Advanced Photonics 2014
DOI: 10.1364/np.2014.nm3a.6
|View full text |Cite
|
Sign up to set email alerts
|

Exploding solitons vs rogue waves in laser cavities

Abstract: Exploding solitons can be found in dissipative systems including laser cavities and reaction-diffusion systems. Certain choice of laser parameters allows us to obtain very high amplitudes during explosions. They can be considered as rogue waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although it was suggested that RSs are exact solutions of the nonlinear Schrödinger (NLS) equation, such as the Akhmediev's breather [9,[15][16][17][18] or the Peregrine soliton [19], or rather solutions of a more general model [20][21][22], there are strong indications that they originate from a combination of higher-order effects such as Raman scattering, selfsteepening, and higher-order dispersions [8,23]. Actually, already in 1989, the appearance of transient pulses that strongly remember rogue wave solitons was identified in Raman systems [24] and, more recently, extreme events (in the form of RSs and rains of solitons) were found in dissipative systems [25][26][27][28][29] and even in integrated optical resonators on chips [30]. The exact role of those effects is still debated, because approaches based on integrable turbulence [17] or the Zakharov-Shabat problem [18] seem to provide insightful results, but a link between the regular NLS dynamics and the observed perturbed evolution is still unclear [31].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was suggested that RSs are exact solutions of the nonlinear Schrödinger (NLS) equation, such as the Akhmediev's breather [9,[15][16][17][18] or the Peregrine soliton [19], or rather solutions of a more general model [20][21][22], there are strong indications that they originate from a combination of higher-order effects such as Raman scattering, selfsteepening, and higher-order dispersions [8,23]. Actually, already in 1989, the appearance of transient pulses that strongly remember rogue wave solitons was identified in Raman systems [24] and, more recently, extreme events (in the form of RSs and rains of solitons) were found in dissipative systems [25][26][27][28][29] and even in integrated optical resonators on chips [30]. The exact role of those effects is still debated, because approaches based on integrable turbulence [17] or the Zakharov-Shabat problem [18] seem to provide insightful results, but a link between the regular NLS dynamics and the observed perturbed evolution is still unclear [31].…”
Section: Introductionmentioning
confidence: 99%
“…Soliton explosions were firstly predicted in the framework of the complex cubic-quintic Ginzburg-Landau equation (CQGLE) 1 , emphasizing that highorder nonlinear terms are crucial to make a soliton explode. Later on, several numerical investigations have been carried out [2][3][4][5] , trying to better understand the intrinsic mechanisms involved in soliton explosions and subsequent revivals of the soliton.…”
mentioning
confidence: 99%